ANALISIS MOTIVASI BELAJAR SISWA KELAS XI IIA DI MAN 1 PANGKALPIANG MASA PANDEMI COVID 19 - Rama Armedi (Universitas Islam Nahdlatul Ulama Jepara, 2022)
ABSTRACTThis research was taken based on the problem of analyzing the learning motivation of class XI IIA students in Man 1 Pangkalpinang during the Covid 19 pandemic, an alternative was needed to increase student learning motivation. This study aims to analyze the learning motivation of Man 1 Pangkalpinang students during the Covid-19 pandemic. Due to the covid-19 pandemic, which caused the learning system in educational institutions to be changed to an online or online learning system. This research uses descriptive-based quantitative research, using a purprosive sampling technique. The population in this study were students of class XI majoring in IIA at MAN 1 Pangkalpinang in the 2019/2020 school year. This research was conducted at MAN 1 Pangkalpinang. This research data collection technique using a questionnaire, the results of the questionnaire provide an overview of the learning motivation of students in MAN 1 Pangkalpinang. From the research results, motivation to learn using descriptive statistics, namely low, medium and high. Of course, the data obtained about the analysis of learning motivation of class XI IIA students at MAM 1 Pangkalpinang can be said to be good and significant with the existing theory.Keywords: Motivation to learn, MAN students, the Covid 19 pandemic. ABSTRAKPenelitian ini diambil berdasarkan permasalahan tentang analisis motivasi belajar siswa kelas XI IIA di Man 1 Pangkalpinang pada masa pandemi covid 19 ini diperlukan sebuah alternatif untuk meningkatkan motivasi belajar siswa. Penelitian ini bertujuan untuk menganalisis motivasi belajar siswa Man 1 pangkalpinang pada masa pandemi covid-19. Karena adanya pandemi covid-19 ini, yang menyebabkan sistem pembelajaran pada lembaga pendidikan diubah menjadi sistem pembelajaran online atau dalam jaringan. Penelitian ini menggunakan penelitian kuantitatif berbasis deskriptif, dengan menggunakan teknik purprosive sampling . Populasi dalam penelitian ini adalah siswa kelas XI jurusan IIA di MAN 1 Pangkalpinang tahun pelajaran 2019/2020. Penelitian ini dikakukan di MAN 1 Pangkalpinang. Teknik pengumpulan data penelitian ini menggunakan kuesioner, dari hasil kuesioner tersebut memberikan gambaran pada motivasi belajar siswa MAN 1 Pangkalpinang. Dari hasil penelitian motivasi belajar menggunakan descrivtive statistics yaitu rendah, sedang dan tinggi. Tentunya, data yang yang didapatkan tentang analisis motivasi belajar siswa kelas XI IIA di MAM 1 Pangkalpinang dapat dikatakan baik dan signifikan dengan teori yang ada.Kata Kunci: Motivasi, Siswa MAN, Pandemi Covid 19.